Pengaruh Job Description, Self Efficacy, dan Iklim Organisasi terhadap Produktivitas Karyawan di PT. Multi Terminal Petikemas Belawan - Siahaan, Maya; Brina, Melda (INDO PUBLISHING, 2026)
This study aims to analyze the impact of job description, self efficacy, and organizational climate on employee productivity at PT. Multi Terminal Petikemas Belawan. This research uses a quantitative approach with descriptive and analytical design. The population of this study consists of all employees at PT. Multi Terminal Petikemas Belawan, with a sample taken using purposive sampling. Data was collected through questionnaires distributed to 100 respondents. The data analysis method used is multiple regression analysis to examine the relationship between job description, self efficacy, organizational climate, and employee productivity. The results show that job description and self efficacy have a significant impact on employee productivity, while organizational climate also plays a key role in enhancing work productivity. Based on these findings, it is recommended that the company continues to improve clear job descriptions, enhances self efficacy among employees, and creates a supportive organizational climate to boost employee productivity. This study is expected to contribute to the company in formulating policies to improve employee performance through better management of job descriptions, self efficacy, and organizational climate.